Analysis of Vocabulary Learning Process from Instagram and TikTok - Fauziah, Nita; Pebriano, Nor Angga; Murtiningsih, Tenny (Universitas Muhammadiyah Surakarta, 2023)
This research explores the effectiveness of Instagram and TikTok as aids for enhancing students' English vocabulary acquisition. Instagram has instructional accounts that routinely publish English learning videos and introduce new vocabulary. TikTok offers exciting content that can aid in vocabulary acquisition but consumes significant data due to its video-centric design. The research investigated vocabulary learning processes and methods in both platforms in depth using a qualitative methodology and a case study design. Six English majors from a private university in South Borneo were asked to participate in this study because they had mastered English vocabulary through autonomous Instagram and TikTok use. Students saved vocabulary-related photos from these platforms to review them later. In addition, participants used the taught language in their regular activities to improve recall and employed mobile phone notes for additional practice. The urge to keep up with popular slang on Instagram and TikTok significantly motivates students to acquire new vocabulary. This indirect pursuit of slang language helps their speaking skills and reading, writing, and listening comprehension. This study highlights the importance of Instagram and TikTok in enhancing students' English vocabulary. Students can improve their language competence by utilizing educational accounts and enjoying these platforms' dynamic content. These findings have substantial implications for educators and students in the digital age who seek automated approaches to enhance language learning.